2013
DOI: 10.1111/are.12163
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ibuprofen on female and male reproduction of the open thelyca marine shrimp,Litopenaeus

Abstract: A research was designed to explore the effect of ibuprofen (IBU) as an intervening agent for prostaglandin biosynthesis on male and female reproduction of three species of Litopenaeus. Ovarian maturation was studied in L. stylirostris and L. vannamei injected periodically with IBU at 0.01 and 0.1 μg g−1 body weight (b.w.) and treated for unilateral eyestalk ablation. IBU at 0.1 μg induced a statistically (P < 0.05) higher rate of L. vannamei females with developing ovaries (45 ± 19%) as compared with controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
(105 reference statements)
0
9
0
2
Order By: Relevance
“…One reason for the reduction in egg produced may be that Ibuprofen affected the egg development in the bed bugs. AlfaroMontoya [21] has shown that Ibuprofen negatively affected marine shrimp ovaries. Tesh and Guzman [40] fed three mosquito species various concentrations of ivermectin in human blood and recorded mortality and effect on fertility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for the reduction in egg produced may be that Ibuprofen affected the egg development in the bed bugs. AlfaroMontoya [21] has shown that Ibuprofen negatively affected marine shrimp ovaries. Tesh and Guzman [40] fed three mosquito species various concentrations of ivermectin in human blood and recorded mortality and effect on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…There were studies on the impact of Ibuprofen on aquatic life, such as in Daphnia magna Mueller, Litopenaeus spp. Farfante and Planorbis carinatus Muller [19][20][21][22]. Heckmanna et al [19,20] revealed that the population growth rate in water fleas (Daphnia spp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En los machos, el ibuprofeno no ejerció ningún efecto sobre el recuento espermático y el peso del espermatóforo, sin embargo, redujo el número de anomalías espermáticas en L. occidentalis y L. stylirostris y mejoró la renovación del espermatóforo en L. stylirostris. Los hallazgos de esta investigación apoyan la hipótesis de que las prostaglandinas están implicadas en la reproducción de peneidos (Alfaro-Montoya, 2015).…”
Section: Líneas De Investigación Desarrolladas § Moluscosunclassified
“…Además, se logró descubrir la localización de la glándula androgénica en varias especies de camarones (Alfaro-Montoya & Hernández, 2012), lo que permitirá disponer de una base anatómica precisa para la manipulación y el estudio de esta importante glándula que controla la masculinidad en los crustáceos. También se está investigando el papel de las prostaglandinas, cuya función en el control de la reproducción de estos animales marinos no ha sido establecida (Alfaro-Montoya, 2013). Finalmente, se está desarrollando la tecnología de reversión sexual y producción de larvas 100% hembras, de mayor tasa de crecimiento, aplicando técnicas de manipulación sexual y biología molecular en L. vannamei.…”
Section: La Investigación Científicaunclassified